Hadith #1114 - Sahih Muslim - Abu al-Zanad أبو الزناد (Sahih Muslim)
I saw the Messenger of Allah (ﷺ) saying the prayer while he was carrying Umama, daughter of Zainab, daughter of the Messenger of Allah (ﷺ). and Abu’l-‘As b. al-Rabi’. When he stood up, he took her up and when he prostrated he put her down, Yahya said: Malik replied in the affirmative.
Grade: Sahih

Hadith #4160 - Sahih Muslim - Abu al-Zanad أبو الزناد (Sahih Muslim)
” Every one of them giving birth to a child, who would have fought in the cause of Allah.”
Grade: Sahih